DEVELOPMENT AND VALIDATION OF A NEW RP-HPLC METHOD FOR SIMULTANEOUS DETERMINATION AND QUANTIFICATION OF SOFOSBUVIR AND DACLATASVIR - Syed Hassan Murtaza; Ahmed Umer Sohaib Ahmed; Tassawer-e-Meran; Sonam Anees; Najam-ul-Hassan Khan; Kishwar Sultana (International Journal of Pharmacy & Integrated Health Sciences)
Background: Sofosbuvir (SOF) and daclatasvir (DCV) are usually prescribed in combination for the treatment of hepatitis C worldwide. Objectives: In the present study a novel, simple, rapid, and cost-effective reversed-phase high performance liquid chromatography (HPLC) method was developed, optimised, and validated for simultaneous analysis of sofosbuvir and daclatasvir in human plasma as well as in solid dosage forms. Methodology: The chromatographic analyses were carried out using Shimadzu HPLC gradient system (LC20), while the other HPLC system used for the peak purity and repeated validation studies was Agilent 1260 Infinity fitted with diode array detector. The column used was C18 (150 × 4.6 mm; 5 µm), from Agela Technologies. The mobile phase consisted of acetonitrile and 0.02 M potassium Hexafluorophosphate buffer (42:58, v/v) at pH 2.7, pumped at the rate of 1.3 mL min−1. The limit of detection and limit of quantification were determined using dilution method (RSD/m formula). Results: SOF and DCV combination therapy is significant for the treatment of hepatitis C. Development of this RP-HPLC method for the simultaneous determination and quantification of SOF and DCV is a part of an extensive project of novel formulation development (fixed dose combination tablets of SOF and DCV). This method is successfully applied for raw materials as well as in combination tablets. This method may also be applied for the quantification of sofosbuvir and daclatasvir in blood samples of patients taking these two antivirals for hepatitis C treatment. Conclusion: The optimized method was successfully applied for the determination of sofosbuvir and daclatasvir in single run without any interference. Hence, the developed method is quite appropriate for the simultaneous determination of SOF and DCV in solid dosage form as well as in human plasma for clinical research studies.